Neurological outcomes in children with and without amalgam-related mercury exposure: seven years of longitudinal observations in a randomized trial - Lauterbach, Martin (2018)
Background. Although large-scale, randomized trials involving children have been completed and their results demonstrate an absence of neurobehavioral effects from clinical exposure to mercury amalgam, neurological findings from such studies have not been reported. Methods. The authors conducted a randomized, prospective trial examining the safety of dental amalgam in which 507 children aged 8 through 12 years were assigned to treatment with either amalgam or resin-based composite. During seven years of follow-up, the authors performed annual clinical neurological examinations, including an evaluation of neurological hard signs (NHSs), presence of tremor and neurological soft signs (NSSs). Results. The authors found no significant differences between treatment groups in any of the neurological measures. Groups did not differ with respect to the presence or absence of NHSs or tremor, nor the presence or absence or severity of NSSs at any point. As expected, NSS severity scores diminished with increasing age. Conclusions. Even at the levels of amalgam exposure in this study (a mean of 7.7-10.7 amalgam surfaces per subject across the seven years of follow-up), the authors conclude that exposure to mercury from dental amalgam does not adversely affect neurological status. Clinical Implications. The current evidence is that potential neurobehavioral or neurological effects from dental amalgam mercury exposure in children are inconsequential.